Pengabdian Kepada Masyarakat Melalui Kegiatan Kuliah Kerja Nyata (KKN) Di Desa Paluh Sibaji - Nurasyah; Fadryan Reynal Zikri; Yofita Intan Putri Kasih Nduru; Nurika Aulia; Yofita Kurnia Gulo; Lhufiah Az Zahra (Hikamatzu | Journal of Multidisciplinary, 2024)
Scientific article of community service entitled "Optimizing Potential to Realize Sustainable and Competitive Villages Through Harmonious Rights in the Framework of Education, Health, Economy, Environmental Management and Religion. Through real work lectures KKN is one form of student contribution to overcome problems that exist in society. This study aims to examine the role of KKN in increasing environmental awareness and providing education to children in Paluh Shibaji Village, Deli Serdang Regency. The method used in this study is observation. KKN students participate in Koran reading activities, provide information counseling on career development, make cholesterol-lowering juice, plant family medicinal plants, provide education about the importance of saving to school children, and participate in mutual cooperation activities. The results of the study showed that through KKN, Paluh Shibaji Village is one of the villages in Deli Serdang Regency. Its location is close to the coast. This village has abundant marine natural resource potential, most of their sea catch is sold at the Labu Beach Fish Landing Place